Developing English Speaking Module By Using Indonesian Local Culture Content: A Quasi-experimental Study For Efl Students In Indonesia - Hakim, Muhammad Arif Rahman (2021)
The purpose of this study was to develop an English-speaking module by using Indonesian culture content and to investigate the effectiveness of the module on EFL students in Indonesia speaking achievement in EFL speaking class in terms of fluency and coherence, lexical resource, grammatical range and accuracy and pronunciation. To that end and for research data collection purposes, the researcher applied quasi-experimental research methodology. ADDIE model is used as an approach in module development. The result of development product is An English speaking module based on Indonesian local culture, which consist with 12 chapters. All of the topics in the module are adapted from various types of culture that reflect Indonesian characteristics such as folklore, traditional arts, and regional names. The study samples consisted of 56 EFL students in the third year students who were equally distributed over two study groups; (experimental and control) and were purposefully chosen to participate in an intervention that lasted for 14 teaching meeting. The study was concluded that students who were taught by using the speaking module based on Indonesian local culture content (experimental group) achieved speaking score better than those who were taught by only using the conventional module (control group). Therefore, the researcher recommends that English teachers or English lecturers who conduct EFL speaking class using local culture contents due to its benefits discussed in this study.